Pulmonary Mucormycosis as the Leading Clinical Type of Mucormycosis in Western China - Junyan Qu (Frontiers Media S.A., 2021)
The aim was to better understand the clinical characteristics of patients with mucormycosis in western China. We retrospectively investigated the clinical, laboratory, radiological and treatment profiles of mucormycosis patients during a 10-year period (2010–2019). As a result, 59 proven mucormycosis were enrolled in this study. It was found that 52.5% of patients had worse clinical outcomes. Pulmonary mucormycosis (PM) was the most common clinical manifestation. The most frequent risk factor was diabetes mellitus (38, 64.4%) for mucormycosis patients. Cough (43, 93.5%), fever (24, 52.2%) and hemoptysis/bloody phlegm (21, 45.7%) were the most common manifestations of PM. There were no differences in clinical manifestations, risk factors and laboratory tests between different clinical outcome groups (P>0.05). Lymph node enlargement (30, 65.2%), patchy shadows (28, 60.9%), cavitation (25, 53.3%) and bilateral lobe involvement (39, 84.8%) were the most common on chest CT. Nodule was more common in good outcome group (P <0.05). A total of 48 cases (81.4%) were confirmed by histopathological examination, 22 cases (37.3%) were confirmed by direct microscopy. PM patients were treated with amphotericin B/amphotericin B liposome or posaconazale had better clinical outcomes (P <0.05). In conclusion, PM was the most common clinical type of mucormycosis in China. Diabetes mellitus was the most common risk factor. PM has diverse imaging manifestations and was prone to bilateral lobes involvement. Early diagnosis and effective anti-mucor treatment contribute to successful treatment.